Development and Study of {99m}Tc-1-Thio-D-glucose for Visualization of Malignant Tumors - Zelchan (Zeltchan) R. V. Roman Vladimirovich; Medvedeva А. А. Anna Aleksandrovna; Sinilkin I. G. Ivan Gennadjevich; Bragina O. D. Olga Dmitrievna; Chernov V. I. Vladimir Ivanovich; Stasyuk (Stasiuk) E. S. Elena Sergeyevna; Rogov A. S. Alexander Sergeyevich; Ilina E. S. Elena Sergeevna; Skuridin V. S. Viktor Sergeyevich (2017, 2017)
Title screen